EFL Teachers’ and Students’ Perspectives on Learner Identity through Project-Based Language Learning in the 21st Century - Duong My Tham; Tran Phan Ngoc Tu (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
Educating students to become 21st century citizens is prioritized in different contexts, and shaping language learners’ identity through project-based learning is one of the requisites to equip learners with 21st century skills. This study, therefore, aims to investigate EFL teachers’ and students’ perspectives on learner identity through project-based language learning (PBLL) in terms of 21st century learning skills in Vietnam. Three hundred and twenty-four students from a high school located in Lam Dong province, Vietnam answered a closed-ended questionnaire, and seven teachers of English participated in semi-structured interviews. The quantitative data obtained from the questionnaire were processed using the SPSS software to calculate mean and standard deviation, while the qualitative data from interviews were analyzed through content analysis. The findings revealed that both EFL teachers and students believed that PBLL could shape and reinforce EFL students’ identities via 21st century learning skills (collaboration, critical thinking, creativity, and communication). Received 5th December 2022; Revised 15th March 2023; Accepted 9th April 2023